Insights into spatial accessibility of primary healthcare in the Cape Town District, South Africa - Africa Ndude; Sinenhlanhla Memela-Radebe (GeoJournal, 2026)
Abstract Access to healthcare is a fundamental human right, yet structural inequalities persist despite public-sector efforts to strengthen primary healthcare. This paper analyses the spatial accessibility of public primary healthcare centres in the Cape Town District, situated in the Western Cape province of South Africa, using Geographic Information Systems (GIS) to model travel distance and time (walking and driving) to these centres. Findings reveal that spatial accessibility in the Cape Town District remains unbalanced, varying across locations, race, age and sex categories. Notably, poor accessibility is highest in the four outer health planning regions: Western, Southern, Northern, and Eastern regions, while the central health planning regions of Klipfontein and Tygerberg have full coverage within 5 km. The black African population is the most affected by poor accessibility, while the proportions of coloured and white populations with poor access are equal. While 82,89% of the population can access primary healthcare within one hour, operational standards are met only when driving a car is the primary mode of transportation to a primary healthcare centre. Furthermore, spatial accessibility varies across demographic groups (children, youth, adults, and the elderly). Intra-regional patterns reflect the district's distinctive spatial structure, in which geographic, socioeconomic, and infrastructural factors shape primary healthcare accessibility. Primary healthcare centres were generally located near referral centres, consistent with operational standards, although accessibility remains limited for individuals without access to motorised transport. Future research in the Cape Town District can assess accessibility at the suburb scale and explore the non-spatial facets of primary healthcare access.